Profitability of animal welfare - Zibolka, Jana (2021)
Increasing numbers of people are concerned about the conditions of farm animal husbandry systems and of the whole meat industry as well as of the welfare of farm animals in Germany. The willingness to pay for animal welfare-friendly products is increasing, while until now there is only one market-based farm animal welfare (FAW) label in Germany, the “Initiative Tierwohl” (ITW). This initiative is the first cross-sectoral alliance of the agricultural industry, the meat industry and the food retailing. The purpose of this on farm-study was to gain insights into the concept of animal welfare and to analyze the economic effects on a farm with fattening pigs participating in the ITW. Further, the farmer´s evaluation about current challenges in the fattening pig sector as well as his motivation for implementing higher FAW standards were examined. Five methods were applied: a literature review, a qualitative interview, a business segment accounting, an extra-cost accounting and a risk analysis. The results of the literature review showed the need for a uniform definition of FAW, unified measuring tools for FAW and the necessity using participatory approaches developing generalities. In this study four different scenarios were examined: the ITW program phase from 2018 to 2020, the program phase of the ITW from 2021 to 2023, the planned German state label and a control scenario. The analysis regarding the extra costs per pig of the FAW programs demonstrated that the opportunity costs keeping lower amounts of pigs, caused by the space requirements of 10 % and 20 % more space, form the highest cost position. The payed renumerations of 5,10 €/pig and 5,28 €/pig in the ITW-scenarios are enough to cover all incidental extra costs. The planned German label has to face high singular investment costs and a presumed renumeration of 6,00 €/pig would not be enough to cover the extra costs. Participating in the ITW leads to reduced fluctuations of the contribution margin of about 11 %, also called hedging effectiveness. Analyzing economic effects of FAW programs on farms represents an instructive approach to reflect the design of such a program. Further research is needed to analyze which factors determine the profitability of FAW programs the most. Risk-reducing effects of higher FAW standards have to be examined more in detail, for instance including potential positive synergies between FAW and animal health. Considering farmers´ individual risk attitudes will give more concrete recommendations for action in the end.